Home-value insurance and idiosyncratic risks of residential property prices - Teye, Alfred Larm (A+BE | Architecture and the Built Environment, 2018)
The recent Global Financial Crisis has reawakened home-owners to the need for protecting their home-equities from possible future house price decline. This paper re-examines the Shiller and Weiss (1999) home-value insurance scheme and proposes a modification that eliminates a large proportion of the idiosyncratic sale price risks of residential properties. Using data between 1995 and 2014 for Amsterdam, the proposed insurance policy shows a higher pay-out efficiency, a higher loss coverage and a greater pay-out probability than the original Shiller and Weiss (1999) scheme. The new home-value insurance policy thus provides better protection for the property sale price risks.